Domestic sewage as a sustainable freshwater substitute for enhanced anaerobic digestion of lignocellulosic biomass - TG Induchoodan; Nimitha Choran; Ajay S. Kalamdhad (Scientific Reports)
Abstract Biochemical methane potential tests using water hyacinth (WH), pretreated water hyacinth (PWH), and Hydrilla verticillata (HV) as substrates using sewage media were explored. This study replaced the freshwater required to prepare the slurry for AD of organic solid waste with domestic sewage. Cow dung was used as the inoculum. WH (241.5 mL CH4/g VSadded), PWH (200.5 mL CH4/g VSadded), and HV (212 mL CH4/g VSadded) produced significant amounts of methane in the sewage medium. 16S-rRNA analysis showed that, in sewage, ~ 85% of the microbes were hydrolytic bacteria, and 7% were methanogens. This abundant quantity of hydrolytic microbes from sewage accelerated lignin degradation, achieving 28.32% and 38.34% degradation for WH and HV, respectively, within 14 days. Field emission-scanning electron microscopy images visually confirmed the enhanced substrate degradation in the presence of sewage. The net energy produced from the AD of WH and HV was significant (4664 J/g VSadded and 4109 J/g VSadded), but for PWH, it was negative, indicating that using sewage medium may be better than costly pretreatment techniques. This study demonstrated the potential of using sewage as an alternative to freshwater in AD, offering a sustainable solution for freshwater conservation and the possible utilisation of sewage for improved methane production, especially for substrates with lignin that are difficult to degrade.